Optimization of the phantom parameters for diffuse optical fluorescence tomography of biotissues in vivo - Samtsov, Michael P.; Tarasov, Dmitriy S.; Goryashchenko, Alexander S.; Kazachkina, Natalia I.; Zherdeva, Victoria V.; Savitsky, Alexander P.; Meerovich, Irina G. (Journal of the Belarusian State University. Physics, 2018)
The paper presents the results obtained in studies of the conditions ensuring correct recording of the concentration of the photosensitizer based on a new indotricarbocyanine dye in biotissues in vivo with the use of a diffuse fluorescence tomograph. When the dye concentration in 50 % blood serum is 4 mmol/l, the fluorescence lifetime is τf = 1.44 ns and in 5 % bovine serum albumin it comes to τf = 1.41 ns, and the kinetics of fluorescence decay are single-exponential. It is demonstrated that, when a concentration of the dye is 40 mmol/l, in the solution one can observe not only monomers but also nonluminescent H-aggregates, with the absorption band overlapping the fluorescence spectrum of monomers. As a result, there is a possibility for nonradiative transfer of the electronic excitation energy from monomers to the nonluminescent associates leading to a decrease of the molecular fluorescence lifetime down to 1.18 ns. It has been found that an ideal medium to prepare a solution for the phantom is blood serum with the dye concentration below 4 mmol/l.